Kajian Konstruksi Gender Dalam Film 500 Days of Summer Melalui Analisis Teori Performativitas Gender Judith Butler - Syahru Ramadhan Awaluddin Fitroh; Melati Budi Srikandi; Anak Agung Istri Agung Maheswari; Kadek Devi Kalfika Anggria Wardani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines gender performativity in the film 500 Days of Summer using Judith Butler’s theory of gender performativity as the main analytical framework. Butler argues that gender is not an inherent identity but a social construct formed through repeated actions, language, and everyday expressions. This qualitative research analyzes how the characters Summer Finn and Tom Hansen represent gender construction through dialogue, cinematic visuals, and symbolic elements presented throughout the narrative. Data were collected from dialogue scripts, visual components such as expressions, gestures, framing, lighting, and costumes, as well as symbolic signs supporting the interpretation of gender. The analysis shows that the film consistently presents a reversal of traditional gender norms. Summer is portrayed as an independent, rational, and dominant woman, while Tom is depicted as emotional, sensitive, and passive. This configuration reinforces Butler’s concept that gender is fluid, unstable, and produced through repeated social practices. The findings indicate that 500 Days of Summer not only offers a romantic storyline but also provides a critique of traditional stereotypes of masculinity and femininity through the performativity of its two main characters. This research is expected to enrich studies on gender representation in film and create space for broader discussions on the construction of gender identity in popular culture.